2004
DOI: 10.1038/sj.ijir.3901223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress on female rat sexual function

Abstract: This study was undertaken to investigate whether prolonged stress interferes with sexual behavior and changes biochemical and physiologic mechanisms. Experiments were repeated three times with different rats in each period. In all, 63 female Sprague-Dawley rats were employed, with 21 rats in each period, and the control group was maintained at room temperature with free access to food and water. The stress group was maintained under a scheduled stress condition for 10 days, and seven rats from the group were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Clinical observations and experimental studies have shown that stress suppresses the sexual/reproductive function (5). While the effects of psychological stress on females have been well studied (6,7), comparatively little is known about the impact of emotional stress on males.…”
Section: S Eskiocak Et Almentioning
confidence: 99%
“…Clinical observations and experimental studies have shown that stress suppresses the sexual/reproductive function (5). While the effects of psychological stress on females have been well studied (6,7), comparatively little is known about the impact of emotional stress on males.…”
Section: S Eskiocak Et Almentioning
confidence: 99%
“…Diabetic state and lack of insulin production also inhibit aromatase activity which is an insulindependent enzyme essential for the conversion of 4-androstenedione and testosterone to estrone and estradiol causing a decrease in estrogen biosynthesis and an increase in testosterone level (Yoon et al, 2005). The alteration of the estrogen and testosterone levels can cause an imbalance in the hypothalamic-hypophyseal-gonodal axis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various forms of stress models such as restraint or mental are known to cause organic responses. Several studies have examined the relationship between stress and sexual behavior in both male and female rats (Sato et al 1996;Bodie et al 2003;Yoon et al 2005). In these studies it has been reported that sexual dysfunction occurs due to complex changes of serum sex hormones, catecholamines and NOS subtype expressions in the vaginal tissues and at the cerebral area (Sato et al 1996;Yoon et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the relationship between stress and sexual behavior in both male and female rats (Sato et al 1996;Bodie et al 2003;Yoon et al 2005). In these studies it has been reported that sexual dysfunction occurs due to complex changes of serum sex hormones, catecholamines and NOS subtype expressions in the vaginal tissues and at the cerebral area (Sato et al 1996;Yoon et al 2005). However, in our literature review we did not find any published study investigating the changes of penile erection and cavernosal tissues due to physical stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation